1972
DOI: 10.1097/00006842-197211000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Adjustment of Burn Patients During Hospitalization

Abstract: The relationship of a variety of premorbid emotional and physical factors to the adjustment of burn patients during hospitalization is examined. Patients were considered to have adjusted poorly if they developed marked regression, severe depression, delirium or unmanageable behavior. Prior physical problems and premorbid psychopathology were found to be significantly more frequent among those who adjusted poorly than those who adjusted well, while greater severity of burn appeared to contribute to development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 10 publications
2
38
0
Order By: Relevance
“…If we regard fighting spirit as an active coping strategy, our results are consistent with those of other studies (Andreasen, Noyles, & Hartford, 1972;Felton & Revenson, 1984) showing that active coping is associated with better long-term adjustment after a serious illness. Fighting spirit may function as an emotion-focused "attention dcployment" strategy (Lazarus, Averill, & Opton, 1974), dcflccting a person's attention from pessimistic and distressing thoughts about illness to more optimistic thoughts that enable the person to dcal actively with the stressor.…”
Section: Resultssupporting
confidence: 91%
“…If we regard fighting spirit as an active coping strategy, our results are consistent with those of other studies (Andreasen, Noyles, & Hartford, 1972;Felton & Revenson, 1984) showing that active coping is associated with better long-term adjustment after a serious illness. Fighting spirit may function as an emotion-focused "attention dcployment" strategy (Lazarus, Averill, & Opton, 1974), dcflccting a person's attention from pessimistic and distressing thoughts about illness to more optimistic thoughts that enable the person to dcal actively with the stressor.…”
Section: Resultssupporting
confidence: 91%
“…Bergamasco et al [21] found that burn victims tried to hide their sequelae with appropriate clothes and, when this was not possible, social isolation was an alternative. Under these conditions, these persons usually report changes in leisure activities [20][21][22][23], which are more marked among victims with visible sequelae, such as on the face and hands, for example. In this study, changes in leisure activities were more frequently reported by participants with burns in visible areas such as the face, neck and lower limbs, all of which are generally exposed during leisure activities.…”
Section: Discussionmentioning
confidence: 99%
“…Andreasen et al [1] considered adjustment was a function of the severity of burn. Total burn area as affecting outcome and adjustment for the child has been identified by Woodward, [2] and Stoddard et al [3], and for the mother [4][5][6], but has been unsupported by the research of Kaim-Caudle and Potter, [7], Benians [8], and Knudson-Cooper [9], Sawyer et al [10], Browne et al [11], Blakeney et al [12][13][14].…”
Section: Introductionmentioning
confidence: 99%